Adult-onset non-5q proximal spinal muscular atrophy: a comprehensive review - Pinto, Wladimir Bocca Vieira de Rezende; Souza, Paulo Victor Sgobbi de; Badia, Bruno Mattos Lombardi; Farias, Igor Braga; Albuquerque, José Marcos Vieira de, Filho; Gonçalves, Eduardo Augusto; Machado, Roberta Ismael Lacerda; Oliveira, Acary Souza Bulle (Arquivos de Neuro-Psiquiatria, 2021)
Background: Adult-onset spinal muscular atrophy (SMA) represents an expanding group of inherited neurodegenerative disorders in clinical practice. Objective: This review aims to synthesize the main clinical, genetic, radiological, biochemical, and neurophysiological aspects related to the classical and recently described forms of proximal SMA. Methods: The authors performed a non-systematic critical review summarizing adult-onset proximal SMA presentations. Results: Previously limited to cases of SMN1-related SMA type 4 (adult form), this group has now more than 15 different clinical conditions that have in common the symmetrical and progressive compromise of lower motor neurons starting in adulthood or elderly stage. New clinical and genetic subtypes of adult-onset proximal SMA have been recognized and are currently target of wide neuroradiological, pathological, and genetic studies. Conclusions: This new complex group of rare disorders typically present with lower motor neuron disease in association with other neurological or systemic signs of impairment, which are relatively specific and typical for each genetic subtype.
Keywords: Muscular Atrophy, Spinal; Neurodegenerative Diseases; Motor Neuron Disease; Neuromuscular Diseases